Communication service priority in smart substation and its queue scheduling method - Jun’e LI; Qiuyu LU; Jian LIU; Kai YUAN; Wei TIAN; Bijun PENG (Tongxin xuebao)
The future development of power grid puts forward the requirement of unified network for all the communication services in smart substation.In order to meet the different quality of service (QoS) requirements of various communication services, as well as ensure the real-time and reliability of key services when the network congestion occurs, a priority scheme and its queue scheduling method for the smart substation was proposed.The priorities of the communication services in the smart substation were assigned considering the delay requirements, the importance to power grid operation control, and the traffic of the communication services.The queue scheduling algorithm of hierarchical deficit weighted round robin (HDWRR), combining the advantages of strict priority queue (SPQ) algorithm and deficit weight round robin (DWRR) algorithm, was designed for the proposed priority scheme.The simulation results show that the proposed method has isolation ability for malicious traffic, and can ensure the real-time and reliable transmission of key services in smart substation once the network is congested.